2019
DOI: 10.21276/ijcmr.2019.6.9.32
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Awareness and Academic Achievement of Medical Students in Different Medical Colleges of Lahore, Pakistan

Abstract: Introduction: To determine medical students' metacognitive awareness and its impact on their academic performance. Study design: Cross-sectional analytic study. Place and Duration of Study: Two different private medical College's from Lahore. From March 2016 to September 2016. Material and Methods: Study was done among second year students of two private medical colleges in Lahore. Students' first year academic achievement information was collected and they also filled the semi-structured questionnaire on meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Our study proved that academic performance and metacognitive score are significantly related. Similar findings reported in another [17] study conducted at Lahore…”
Section: Discussionsupporting
confidence: 91%
“…Our study proved that academic performance and metacognitive score are significantly related. Similar findings reported in another [17] study conducted at Lahore…”
Section: Discussionsupporting
confidence: 91%
“…14 A significant correlation has been found between knowledge and regulation of cognition. 15 Evidence has been shown that this inventory can help differentiate between more and less experienced students. The adult learners differ from inexperienced students in their use of metacognitive regulatory skills.…”
Section: Figure-1: Difference Of Mean Among Males and Females In Doma...mentioning
confidence: 99%